2018
DOI: 10.1152/ajpheart.00335.2018
|View full text |Cite
|
Sign up to set email alerts
|

Hypercapnia-induced shear-mediated dilation in the internal carotid artery is blunted in healthy older adults

Abstract: This study aimed to elucidate the effect of aging on shear-mediated dilation of the common and internal carotid arteries (CCA and ICA, respectively). Hypercapnia-induced shear-mediated dilation in the CCA and ICA were assessed in ten young (5F/5M, 23±1 years) and ten older (6F/4M, 68±1 years) healthy adults. Shear-mediated dilation was induced by two levels of hypercapnia (target end-tidal carbon dioxide; +5 and +10mmHg from individual baseline value) and was calculated as the percent rise in peak diameter fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 45 publications
2
27
1
Order By: Relevance
“…Although CVR tests are often interpreted as assays of cerebrovascular endothelial function (e.g. Ainslie et al 2007;Lavi et al 2006) and measurement of ICA diameter change during steady-state CVR tests taken to be representative of shear-mediated dilatation (Iwamoto et al 2018a(Iwamoto et al ,b, 2020Suzuki et al 2020), the current study found no relationship between CVR of Q ICA and cFMD diameter change (r 2 = 0.06; P = 0.46, Fig. 4C).…”
Section: Correlational Analysescontrasting
confidence: 53%
See 2 more Smart Citations
“…Although CVR tests are often interpreted as assays of cerebrovascular endothelial function (e.g. Ainslie et al 2007;Lavi et al 2006) and measurement of ICA diameter change during steady-state CVR tests taken to be representative of shear-mediated dilatation (Iwamoto et al 2018a(Iwamoto et al ,b, 2020Suzuki et al 2020), the current study found no relationship between CVR of Q ICA and cFMD diameter change (r 2 = 0.06; P = 0.46, Fig. 4C).…”
Section: Correlational Analysescontrasting
confidence: 53%
“…Studies by Iwamoto et al . (2018a, 2020) also indicate that there may be no sex differences in ICA vasodilator responses to steady‐state hypercapnia, although differences in methods between those studies and the current study make comparison difficult. Given that the effect of menstrual cycle on vascular function in general remains controversial (e.g.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…We averaged continuously measured hemodynamic variables of the initial 2 min (baseline) and of the 10 s before peak ICA diameter during the hypercapnia condition. We then analyzed the diameter and mean blood velocity (V mean ) during FMD tests at 30 Hz using custom-designed edge-detecting and wall-tracking software (version 2.0.1, S-13037, Takei Kiki Kogyo) (Iwamoto, Bock, & Casey, 2018b). We detected brachial artery data using an algorithm reported previously (Black, Cable, Thijssen, & Green, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…We detected brachial artery data using an algorithm reported previously (Black, Cable, Thijssen, & Green, 2008). We interpolated ICA data to 1 Hz and filtered them using the two-stage filtering process (median filter and Savitzky-Golay finite impulse response smoothing filter) (Iwamoto et al, 2018b) with custom software (Python version 3.6.1, Python Software Foundation). We calculated SR in the brachial artery and ICA by the equation; 4 × V mean / arterial diameter.…”
Section: Discussionmentioning
confidence: 99%